A focus on disciplinary language: Bringing critical perspectives to reading and writing in science. Issue 1 (2nd January 2020) - Moore, Jason; Schleppegrell, Mary
ABSTRACT: In this article, we show how close attention to language throughout a socio-scientific investigation supports upper elementary Arabic-speaking students to learn English while participating in valued disciplinary practices in science. Engagement in reading and writing with a focus on language also enables them to bring critical perspectives to the ways authors calibrate their presentation of evidence and present different degrees of certainty, and challenge each other's arguments as they offer their own points of view. A focus on language in such disciplinary practices transcends a generic understanding of academic language and attends to the knowledge to be developed in schooling and the role of language in enacting disciplinary meanings and practices; it also enables students to bring their own voices to learning.